2019
DOI: 10.29374/10.29374/2527-2179.bjvm102919
|View full text |Cite
|
Sign up to set email alerts
|

M-mode echocardiography measurements of healthy Brazilian random bred cats

Abstract: To determine the M-mode echocardiography reference measurements for Brazilian random bred cats in Rio de Janeiro, Brazil, cats presenting for routine care were examined by M-mode echocardiography. Animals with free wall values of the left ventricle and/or interventricular septum above 5 mm were not included. A total of 125 cats with were included in the study. The correlation of the body score condition (BSC) with the echocardiography measurements was positive for left ventricle wall in systole (LVWs) and left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the studies of Ward et al (2012) the value was 62 + 1.8% for adult cats (1 to 3 years old). Silva et al (2019) carried out a study with 125 mixed-breed cats of varying ages and observed an ejection fraction of around 85.74% ± 7.25 (coefficient of variation 8%). Although there was no proven correlation of age with ejection fraction, it was observed in the present study that 6-month-old cats have values closer to that of adult cats.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of Ward et al (2012) the value was 62 + 1.8% for adult cats (1 to 3 years old). Silva et al (2019) carried out a study with 125 mixed-breed cats of varying ages and observed an ejection fraction of around 85.74% ± 7.25 (coefficient of variation 8%). Although there was no proven correlation of age with ejection fraction, it was observed in the present study that 6-month-old cats have values closer to that of adult cats.…”
Section: Discussionmentioning
confidence: 99%